2014
DOI: 10.1111/ijn.12370
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a rehabilitation programme for Chinese cancer survivors: A pilot study

Abstract: Cancer survivors have experienced high stress which impairs psychological functioning and decreases quality of life (QOL). This study aims to assess the mediating effect of self-efficacy on mood disturbance and QOL, and determine the effectiveness of a 12 week rehabilitation programme to improve self-efficacy as well as improve mood disturbance and QOL in Chinese cancer survivors. A total of 47 cancer patients were randomly assigned into the experimental (n = 24) and control (n = 23) groups. The participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Self-control is perceived control of one’s functions and behavior as central to one’s functioning, and plays a pivotal role in success in life [ 11 ]. Existing literature has shown that self-control enables the overcoming of pathological symptoms or problems in the rehabilitation of cancer survivors [ 22 ]. It also acts as a buffer and a psychological resource among patients who have limited daily activities as a result of physical disabilities [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-control is perceived control of one’s functions and behavior as central to one’s functioning, and plays a pivotal role in success in life [ 11 ]. Existing literature has shown that self-control enables the overcoming of pathological symptoms or problems in the rehabilitation of cancer survivors [ 22 ]. It also acts as a buffer and a psychological resource among patients who have limited daily activities as a result of physical disabilities [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher score of the Hand-Foot Skin Reaction and Quality of Life Questionnaire (HF-QOL) indicates poorer QOL or worsening symptoms[ 15 ]. Self-efficacy plays a positive role in the psychological resilience of breast cancer patients after surgery[ 16 ], which positively correlated with QOL[ 17 ]. To understand QOL and self-efficacy of the patients, we also conducted scale assessments, including HF-QOL and the general self-efficacy scale (GSES).…”
Section: Methodsmentioning
confidence: 99%
“…for not determining a sample size were missing (Yates et al, 2004;Zhang et al, 2016). Turner et al (2019) used a sample size calculation but were not able to recruit enough patients.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…| 2763et al, 2004Zhang et al, 2016), breast (Chambers et al, 2014;Zhang et al, 2016), head and neck (Turner et al, 2019;Yates et al, 2004), prostate (Chambers et al, 2014), haematological (Chambers et al, 2014), (Non-) Hodgkin cancer (Taylor et al, 2019). All studies were conducted in an ambulatory setting.…”
mentioning
confidence: 99%